MENGUAK â€œPANCERâ€ INTEGRITAS AKUNTAN DENGAN FILOSOFI JAWA - Eltivia, Nurafni (Program Studi Akuntansi FPEB UPI, 2013)
Accountant integrity is questioned, when fraud occurs which involves accountants as one of the actors. This paper seeks to explore the Javanese culture in interpreting the character of an accountant with integrity, with the philosophy Sedulur Papat Kalima Pancer. This philosophy means that every human being will be fully human with four energies without ignoring consciousness as the center of everything. There are four figures who are always present in the wayang called the punakawan who came from this philosophy. The character of each of the characters of a punakawan when put together reflects the character of the accountant who excels. Semiotics is a method used in this paper to uncover the